O peso da água: a arte como mecanismo de produção da memória afrodiaspórica - Moura, Camila Carvalho (2022)
This work presents art as a way to elaborate on colonial matters, especially on the contemporary outcomes of the slave trade and enslaving. In order to do so, relies on the theories about coloniality and decoloniality by Aníbal Quijano (2005, 2015), Walter Mignolo (2008, 2011) and Luiz Rufino (2019), and on the elaborations on the consequences of racism on the black psyche by Frantz Fanon (1953) and Grada Kilomba (2008), as well as on bell hooks’ (1992) thoughts on race and representation – among other authors. After a brief conceptualization on colonialism, coloniality and decoloniality, the focus of this analysis resides on the study of artworks that are centered around racial issues: “Barrueco” by Ayrson Heráclito and Danilo Barata (2004), “Assentamento” (2013) by Rosana Paulino and the trilogy “Illusions” (2016, 2018 and 2019) by Grada Kilomba. These works discuss the colonial past in a way it retells the story from a black perspective which allows us to see art as a tool to produce decolonial knowledge and to remedy the trauma that steams from colonialism. I write from the standpoint of a black women about artworks that are centered around black people, focusing on the works of Grada Kilomba. For her work is essentially transdisciplinary in its theme and language, and profoundly concerned with conceiving a new form of producing knowledge from her perspective as a black woman